CC chemokine receptor 5 Δ32 polymorphism: association analysis and allele distribution among cutaneous leishmaniasis patients from Pakistan. (6th April 2016) - Sophie, Mariam; Hameed, Abdul; Muneer, Akhtar; Samdani, Azam J.; Saleem, Saima; Azhar, Abid
Abstract : Background: Human immunodeficiency virus (HIV)/leishmaniasis coinfection is a matter of deep concern worldwide. CC chemokine receptor 5 (CCR5) functions as a co‐receptor for HIV entry into host immune cells with an elevated expression observed during leishmaniasis, promoting parasite persistence. A 32 bp deletion ( Δ32 ) in the CCR5 gene provides protection against HIV infection and increased resistance to Leishmania infection. Methods: In this study, CCR5‐Δ32 distribution within Pakistani population with cutaneous leishmaniasis was investigated to evaluate genetic susceptibility to HIV infection. CCR5‐Δ32 polymorphism was analyzed in 276 leishmaniasis patients and 119 uninfected healthy controls. Genotypic and allelic frequencies were evaluated and tested for Hardy–Weinberg equilibrium (HWE). Results: The overall Δ32 allele frequency was 6.58% of the population (n = 395). There was a significant difference (p < 0.05) in the geographical distribution of Δ32 allele which was higher in the northern region of the country when compared with the south. Five individuals were identified to be homozygous for the Δ32 allele which has not been reported before from Pakistan. However, no significant association was observed between CCR5‐Δ32 and cutaneous leishmaniasis. Conclusion: The higher frequency of CCR5 wild‐type allele among leishmaniasis patients may suggest an increased risk of HIV infection and also support its facilitative role in Leishmania infection.